An assessment of exchange rate impact over Taylor rule determination in Brazil - Costa, Alexis Petri Magalhães (2017)
This work assesses the validity of applying the Taylor Rule to the Brazilian market. Several variables, tools and features were analyzed. Among its variables, inflation, inflation target and output gap were included to determine a basis scenario. On top of that, exchange rates and exchange rate related information was tested. Both the crude market input (spot rate) and a trade-weighted currency are included in this analysis. Also extracted from the market, the carry-trade premium was calculated from future exchange rate quotes. Among its tools, the smoothing factor was evaluated. The series were tested for regime breaks, unit root and cointegration, residual autocorrelation, normality, heteroskedasticity and coefficient linearity. Among its features, special attention was paid to the proper timing of each variable. The regressions being forward looking, it was important to line up the actual information available for the Brazilian Central Bank at the time of each decision. Timing was again a factor when considering different cutoff periods, and for synchronizing market data, especially for constructing the carry-trade payoff. This work concludes that evidence of a Taylor Rule being a response function for the Brazilian Central Bank is shaky, especially given the number of misspecification indicators found. Results also suggest that, assuming there is a need to protect the local economy from sharp capital flows consequent of interest rate changes, the implicit future exchange rate premia is not a good indicator of such risk.